A single-chamber microbial fuel cell as an alternative biosensor for continuous and onsite determination of BOD in wastewater - Ha, Dinh Thi Thu; Phat, Pham Ngoc (Vietnam Journal of Science and Technology, 2024)
The two main pollution parameters, BOD (Biochemical Oxygen Demand) and COD (Chemical Oxygen Demand), are crucial factors in assessing water quality and pollution levels. Currently, COD can be measured using sensor devices, while BOD relies on the activity of microorganisms. Traditionally, the quantification of biologically oxidizable organic carbon involves measuring oxygen consumption over a five-day period, commonly known as the BOD5 test. However, the BOD5 test has several disadvantages, such as its time-consuming nature, unsuitability for process control, and the requirement for highly skilled samplers. It was hypothesized that the output of a single-chamber microbial fuel cell (SCMFC) with an air-cathode could serve as an alternative method for measuring BOD. To validate this hypothesis, this study conducted some experiments using the model of SCMFC. When artificial wastewater, utilizing sodium acetate as fuel, was employed, a strong linear correlation (R2 > 0.99) between the total charge transferred and BOD5 concentration was confirmed. Additionally, the linear relationship was also investigated for real domestic wastewater, resulting in a combined correlation with an R2 value exceeding 0.98. Until now, research on biosensors (particularly SCMFC-based biosensors) in Viet Nam is still relatively new and has not been extensively conducted. The results of this study could provide a solid foundation for the development of continuous and onsite BOD sensors to monitor BOD concentrations in wastewater streams.